Ultrasonic computed tomography imaging of iron oxide nanoparticles. (10th January 2017) - Perlman, Or; Azhari, Haim
Abstract: Iron oxide nanoparticles (IONPs) are becoming increasingly used and intensively investigated in the field of medical imaging. They are currently FDA approved for magnetic resonance imaging (MRI), and it would be highly desirable to visualize them by ultrasound as well. Previous reports using the conventional ultrasound B-scan (pulse-echo) imaging technique have shown very limited detectability of these particles. The aim of this study is to explore the feasibility of imaging IONPs using the through-transmission ultrasound methodology and demonstrate their detectability using ultrasonic computed tomography (UCT). Commercially available IONPs were acoustically analysed to quantify their effect on the speed of sound (SOS) and acoustic attenuation as a function of concentration. Next, through-transmission projection and UCT imaging were performed on a breast mimicking phantom and on an ex vivo tissue model, to which IONPs were injected. Finally, an MRI scan was performed to verify that the same particles examined in the ultrasound experiment can be imaged by magnetic resonance, using the same clinically relevant concentrations. The results have shown a consistent concentration dependent speed of sound increase (1.86 ms − 1 rise per 100 µ g · ml −1 IONPs). Imaging based on this property has shown a substantial contrast-to-noise ratio improvement (up to 5 fold, p < 0.01). The SOS-related effect generated a well discernible image contrast and allowed the detection of the particles existence and location, in both raster-scan projection and UCT imaging. Conversely, no significant change in the acoustic attenuation coefficient was noted. Based on these findings, it is concluded that IONPs can be used as an effective SOS-based contrast agent, potentially useful for ultrasonic breast imaging. Furthermore, the particle offers the capacity of significantly enhancing diagnosis accuracy using multimodal MRI-ultrasound imaging capabilities.